2006
DOI: 10.1038/nature04412
|View full text |Cite
|
Sign up to set email alerts
|

ClpS is an essential component of the N-end rule pathway in Escherichia coli

Abstract: The N-end rule states that the half-life of a protein is determined by the nature of its amino-terminal residue. Eukaryotes and prokaryotes use N-terminal destabilizing residues as a signal to target proteins for degradation by the N-end rule pathway. In eukaryotes an E3 ligase, N-recognin, recognizes N-end rule substrates and mediates their ubiquitination and degradation by the proteasome. In Escherichia coli, N-end rule substrates are degraded by the AAA + chaperone ClpA in complex with the ClpP peptidase (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
278
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(294 citation statements)
references
References 18 publications
14
278
2
Order By: Relevance
“…The reason for this conclusion is that any one of the latter four residues, if made N-terminal, would be directly recognized as a Nd p residue by the ClpS-ClpAP targeting͞proteolytic complex (Fig. 1B) (31). Because the degradation of Asp-␤gal and Glu-␤gal, the substrates of V. vulnificus Bpt, was not affected by the absence of V. vulnificus Aat, and because a converse omission of V. vulnificus Bpt from E. coli expressing V. vulnificus Aat did not perturb the degradation of Aat substrates Arg-␤gal and Lys-␤gal ( Fig.…”
Section: Bpt Transferase Has a Hybrid Recognition͞conjugation Specifimentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this conclusion is that any one of the latter four residues, if made N-terminal, would be directly recognized as a Nd p residue by the ClpS-ClpAP targeting͞proteolytic complex (Fig. 1B) (31). Because the degradation of Asp-␤gal and Glu-␤gal, the substrates of V. vulnificus Bpt, was not affected by the absence of V. vulnificus Aat, and because a converse omission of V. vulnificus Bpt from E. coli expressing V. vulnificus Aat did not perturb the degradation of Aat substrates Arg-␤gal and Lys-␤gal ( Fig.…”
Section: Bpt Transferase Has a Hybrid Recognition͞conjugation Specifimentioning
confidence: 99%
“…Asp-␤gal and Glu-␤gal are normally long-lived in E. coli, because N-terminal Asp and Glu are stabilizing residues in this prokaryote, in that they are not recognized by either the Aat L͞F K,R -transferase or the rest of the E. coli N-end rule pathway (25,26,31). Previous work (13,17,36) has shown that the steady-state level of an X-␤gal reporter is a sensitive measure of its metabolic stability.…”
Section: Bpt Transferase Has a Hybrid Recognition͞conjugation Specifimentioning
confidence: 99%
See 1 more Smart Citation
“…Some bacterial adapter proteins alter substrate preferences. For example, the ClpS adapter protein specifically inhibits the degradation of ssrA-tagged substrates by ClpAP but stimulates ClpAP to degrade aggregated proteins and possibly N-end rule substrates [76][77][78]. The use of adaptors allows for an additional level of regulation of degradation.…”
Section: Adapter Proteinsmentioning
confidence: 99%
“…37 Moreover, other AAAþ proteases interact with multiple types of peptide signals to identify the correct substrates. 7,[38][39][40][41][42][43][44][45] The AAAþ p97 protein also employs its N domain to interact with disparate sequences in a wide variety of adaptors. 46 The peptide-binding versatility exhibited by the ClpX N domain and SspB ensures that ClpXP can recognize many different substrates and adaptors in different ways but with high specificity.…”
Section: Discussionmentioning
confidence: 99%